La divinisation transcendant les limites spatiales et temporelles de l’être créé. Apories et solution ressortissant à l’eschatologie de Maxime le Confesseur - Mueller-Jourdan, Pascal (Warszawskie Studia Teologiczne, 2022)
When it is joined to the Logos at the end of time, the nature of beings will have emerged from the limits that we know at present. But for the thought of Maximus the Confessor, which we will examine here, place and time, which are both the attestation of these limits but also the sine qua non conditions for the being of the beings, will, at the last day, be abandoned in favour of a modality of being which will transcend them definitively. What then of the integrity of nature if what constitutes its essential determinations will have disappeared ? Will we not be in the presence of another nature ? This article should provide some clarity on the status of created nature when it transcends these natural limits and becomes in God, in whom there are no limits.